Populisme Partai Politik Islam dalam Konteks Pemilu 2024 di Kabupaten Lamongan - Moh Sa’diyin (JOSH: Journal of Sharia, 2025)
It is important to develop a clear framework in political education so that people in Lamongan Regency can understand the dynamics of populism and actively participate in the 2024 elections. Thus, this research is expected to make a significant contribution to the understanding of populism and its impact in Lamongan Regency, as well as create a more effective strategy ahead of the 2024 elections. It is important to ensure that all stakeholders are committed to creating an environment that supports constructive dialogue, so that the 2024 elections can run more fairly and inclusively. In the face of the 2024 election, it is important for the public to understand the role of populism in the local political context and its impact on social stability in Lamongan Regency. Inclusive and collaborative political education will help the public understand the issues of populism, so that the 2024 elections in Lamongan Regency can take place more peacefully and constructively. It is important to emphasize that effective political education will empower the community, so that they can contribute positively to facing the challenges of populism and strengthening democracy in Lamongan Regency. Therefore, strong collaboration between all elements of society, including religious organizations and educational institutions, is essential to create collective awareness of populism and its impact in Lamongan Regency.It is important to prioritize further research on the specific impact of populism on voter behavior in Lamongan Regency, in order to formulate a more effective strategy in the upcoming elections.